2011
DOI: 10.3390/w3041112
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation of Castor Bean (Ricinus communis L.) and Sunflower (Helianthus annus L.) Plant Species with Municipal Wastewater Effluent: Impacts on Soil Properties and Seed Yield

Abstract: Abstract:The effects of plant species (castor bean (Ricinus communis L.) versus sunflower (Helianthus annus L.)) and irrigation regime (freshwater versus secondary treated municipal wastewater) on soil properties and on seed and biodiesel yield were studied in a three year pot trial. Plant species were irrigated at rates according to their water requirements with either freshwater or wastewater effluent. Pots irrigated with freshwater received commercial fertilizer, containing N, P, and K, applied at the begin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 44 publications
5
13
0
Order By: Relevance
“…Boron and trace elements are occasionally a concern for the reuse of TME (Angin et al 2005;Pedrero et al 2010). On some occasions, crop yield has been decreased by the application of TME due to toxicity of one or various elements, as reviewed by Pedrero et al (2010) and reported by Chatzakis et al (2011). In this experiment, the concentrations of B, Al, Years of TMW applicaƟon ( Pallic 5 mg P / L Pallic 10 mg P / L Pallic 15 mg P / L Recent 5 mg P / L Recent 10 mg P / L Recent 15 mg P / L Fig.…”
Section: Sodium and Trace Elementsmentioning
confidence: 63%
“…Boron and trace elements are occasionally a concern for the reuse of TME (Angin et al 2005;Pedrero et al 2010). On some occasions, crop yield has been decreased by the application of TME due to toxicity of one or various elements, as reviewed by Pedrero et al (2010) and reported by Chatzakis et al (2011). In this experiment, the concentrations of B, Al, Years of TMW applicaƟon ( Pallic 5 mg P / L Pallic 10 mg P / L Pallic 15 mg P / L Recent 5 mg P / L Recent 10 mg P / L Recent 15 mg P / L Fig.…”
Section: Sodium and Trace Elementsmentioning
confidence: 63%
“…Madejon et al [25] have also reported that the addition of organic materials through municipal solid waste at doses of 50,000 kg ha -1 did not negatively affect the dehydrogenase and urease activities of the soil even at higher availability of heavy metals. Chatzakis et al [11] have shown that activities of dehydrogenase enzyme were enhanced by irrigating the soil with secondary treated waste water effluent as compared to the fresh water irrigated one.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the obtained data from these multiple sources were integrated into GIS to estimate the surface areas of water bodies and the annual evapotranspiration amounts using the estimates from neighboring Lake Nasser and Tushka. The annual water consumption depth of 1900 mm 19 for the castor oil is used to estimate the annual water budget that can be used when the additional cultivations are added in the bare soil areas. The annual surplus amounts of water can then be estimated.…”
Section: Methodsmentioning
confidence: 99%